ATP‐binding cassette transporters and sterol O‐acyltransferases interact at membrane microdomains to modulate sterol uptake and esterification. Issue 11 (28th July 2015) - Gulati, Sonia; Balderes, Dina; Kim, Christine; Guo, Zhongmin A.; Wilcox, Lisa; Area‐Gomez, Estela; Snider, Jamie; Wolinski, Heimo; Stagljar, Igor; Granato, Juliana T.; Ruggles, Kelly V.; DeGiorgis, Joseph A.; et al.
ABSTRACT: A key component of enkaryotic lipid homeostasis is the esterification of sterols with fatty acids by sterol O ‐acyltransf erases (SOATs). The esterification reactions are allosterically activated by their sterol substrates, the majority of which accumulate at the plasma membrane. We demonstrate that in yeast, sterol transport from the plasma membrane to the site of esterification is associated with the physical interaction of the major SOAT, acyl‐coenzyme A:cholesterol acyltransferase (ACAT)‐related enzyme (Are)2p, with 2 plasma membrane ATP‐binding cassette (ABC) transporters: Aus1p and Pdr11p. Are2p, Aus1p, and Pdr11p, unlike the minor acyltransferase, Are1p, colocalize to sterol and sphingolipid‐enriched, detergent‐resistant microdomains (DRMs). Deletion of either ABC transporter results in Are2p relocalization to detergent‐soluble membrane domains and a significant decrease (53‐36%) in esterification of exogenous sterol. Similarly, in murine tissues, the SOAT1/Acat1 enzyme and activity localize to DRMs. This subcellular localization is diminished upon deletion of murine ABC transporters, such as Abcg1, which itself is DRM associated. We propose that the close proximity of sterol esterification and transport proteins to each other combined with their residence in lipid‐enriched membrane microdomains facilitates rapid, high‐capacity sterol transport and esterification, obviating any requirement for soluble intermediary proteins.—Gulati, S., Balderes, D., Kim, C., Guo, Z. A., Wilcox, L., Area‐Gomez, E., Snider, J., Wolinski, H., Stagljar, I., Granato, J. T., Ruggles, K. V., DeGiorgis, J. A., Kohlwein, S. D., Schon, E. A., Sturley, S. L. ATP‐binding cassette transporters and sterol O ‐acyltransferases interact at membrane microdomains to modulate sterol uptake and esterification. FASEB J. 29, 4682‐4694 (2015). www.fasebj.org